Server + Certification Bible (photocopy) - Kay Trevor (Hungry Minds, 2001)
The Server+ Certification Bible is a combination of information drawn right from the Server+ test objectives. It focuses on subject matter mastery, complete with review questions to prepare you for the exam. Topics focus on vendor-neutral knowledge covering multiple server types, server installation procedures, configuration and upgrading, advanced hardware issues, proactive maintenance, network cabling and connecting, troubleshooting, SCSI, multiple CPU's and RAID and will addressed a level of knowledge above basic hardware issues. As with all books in the Certification Bible series, The Server+ Certification Bible relies on logical organization, practice, and real-world examples to facilitate learning beyond the exam.